PENGARUH KONTROL DIRI, JENIS KELAMIN, DAN PENDAPATAN TERHADAP PENGELOLAAN KEUANGAN PRIBADI MAHASISWA PASCASARJANA UNIVERSITAS NEGERI SURABAYA - Herlindawati, Dwi (UNIVERSITAS NEGERI SURABAYA, 2015)
This study aimed to analyze the influence of self-control, gender, and income on personal financial management Universitas Negeri Surabaya Post Graduate student either partially or simultaneously. Research conducted a quantitative study. The population in this study are Post Graduate students of Universitas Negeri Surabaya in 2014 as many as 910 with a total sample of 278 students consisting of 128 male students and 150 female students. Methods of data analysis using multiple linear regression analysis technique. The results showed that partially self-control and earnings significantly influence personal financial management of Post Graduate student Universitas Negeri Surabaya, while gender has no influence on personal financial management of Post Graduate student Universitas Negeri Surabaya. Simultaneously self-control, gender, and income significantly influence personal financial management of Post Graduate student Universitas Negeri Surabaya